2011
DOI: 10.1152/japplphysiol.00009.2011
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral microvascular response to muscle contraction is unaltered by early diabetes but decreases with age

Abstract: Long-term or untreated diabetes leads to micro- and macrovascular complications. However, there are few tests to evaluate microvascular function. A postcontraction blood oxygen level-dependent (BOLD) magnetic resonance imaging (MRI) technique was exploited to measure peripheral microvascular function in diabetics and healthy controls matched with respect to age, body mass index, and physical activity. Postcontraction BOLD microvascular response was measured following 1-s maximal isometric ankle dorsiflexion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…These results are in agreement with significantly reduced steady-state LBF responses during submaximal cycling (15) and leg-extension exercise (16) in humans with T2D. In contrast, Womack et al reported similar large artery or capillary recruitment to submaximal handgrip exercise in uncomplicated diabetes (49), and Slade et al showed similar single dorsiflexion exercise induced peak muscle blood oxygen leveldependent magnetic resonance imaging signals (39). Also, in diabetic animal models, unaltered LBF responses (5) or microvascular PO 2 responses (27) were reported in GK rats and normal capillary flow responses in Zucker diabetic fatty rats (46).…”
Section: Incremental Testsupporting
confidence: 73%
See 1 more Smart Citation
“…These results are in agreement with significantly reduced steady-state LBF responses during submaximal cycling (15) and leg-extension exercise (16) in humans with T2D. In contrast, Womack et al reported similar large artery or capillary recruitment to submaximal handgrip exercise in uncomplicated diabetes (49), and Slade et al showed similar single dorsiflexion exercise induced peak muscle blood oxygen leveldependent magnetic resonance imaging signals (39). Also, in diabetic animal models, unaltered LBF responses (5) or microvascular PO 2 responses (27) were reported in GK rats and normal capillary flow responses in Zucker diabetic fatty rats (46).…”
Section: Incremental Testsupporting
confidence: 73%
“…Considerations for these differences include the different exercise models employed, muscle groups studied, differences in blood flow measurement techniques utilized, and the fact that the GK rat represents a nonhyperinsulinemic diabetic model, whereas human participants are typically hyperinsulinemic. In addition, tissue and/or body mass content was significantly different between those with T2D and controls in some studies (5,49) whereas others matched participants to body composition/mass (15,39).…”
Section: Incremental Testmentioning
confidence: 99%
“…For the evaluation of vascular and muscle diseases it is feasible and worth performing muscle BOLD measurements at higher magnetic field strengths in order to be able to detect more pronounced changes of the muscle BOLD signal time courses. For instance, it could be of value to repeat studies that have demonstrated interesting trends at 1.5 T though not reaching significance level at 3.0 T or even higher field strength to establish significance (7,21). As the availability of 3.0 T MRI devices is increasing, high field muscle BOLD MRI might improve the diagnostics of physiological and pathological alterations of peripheral limb perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition capillary density is also reduced in chronic disease (11, 31) and aging (13, 14). We have previously shown an inverse relationship between age (19–58 years old) and microvascular function of the anterior compartment (AC) using MRI blood oxygen-level dependent (BOLD) (37). In agreement, contraction mediated large artery flow (rapid onset vasodilation) with brief contraction is reduced in elderly adults in the brachial and femoral artery (4, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Functional MRI BOLD imaging of skeletal muscle has been used increasingly over the last decade to examine peripheral microvascular function (23, 37, 41). Skeletal muscle BOLD responses arise largely from changes in blood volume and oxygenation from small veins, i.e.…”
Section: Introductionmentioning
confidence: 99%